Hybrid thermomagnetic oscillator for cooling and direct waste heat conversion to electricity. (1st January 2019) - Deepak, K.; Varma, V.B.; Prasanna, G.; Ramanujan, R.V.
Graphical abstract: Highlights: Coupled device for simultaneous cooling and electricity harvesting using waste heat. Cooling of heat load by 70 °C and voltage of upto 10 V/cycle and 15 mA current/cycle. Thermomagnetic response combined with Electromagnetic induction for first time. Simulation and optimization of device parameters performed for effective voltage output. Abstract: Waste heat is an unavoidable and undesirable product of a huge number of industrially important processes. Cooling of such a heat load is of high interest. We developed a novel hybrid thermomagnetic oscillator (TMO) for cooling of the heat load as well as electricity harvesting. A bulk alloy, with a composition of (MnNiSi)0.7 (Fe2 Ge)0.3 and Curie temperature of 144 °C, was used as the thermomagnetic material. Heat load cooling by mechanical oscillation between the load and the sink by up to 70 °C was achieved. Voltage of up to 10 V/cycle and a current of 15 mA was generated by the mechanical oscillation of this alloy and a coupled permanent magnet through solenoid type Cu coils. This energy was stored in a capacitor and used to light up a LED. The thermomagnetic material transferred heat from the heat load to the heat sink. A moving mesh based numerical model was developed to determine the role of various parameters on the performance. Our simulations are in good agreement with our experimental findings. Superior device performance can be achieved by higher magnetic field strength, sample mass, thermal conductivity of the sample, and optimum device height.